2019
DOI: 10.1186/s42490-019-0008-x
|View full text |Cite
|
Sign up to set email alerts
|

Spiropyran as a potential molecular diagnostic tool for double-stranded RNA detection

Abstract: Background: Long double-stranded RNAs (dsRNAs) are duplex RNAs that can induce immune response when present in mammalian cells. These RNAs are historically associated with viral replication, but recent evidence suggests that human cells naturally encode endogenous dsRNAs that can regulate antiviral machineries in cellular contexts beyond immune response.Results: In this study, we use photochromic organic compound spiropyran to profile and quantitate dsRNA expression. We show that the open form of spiropyran, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…Therefore, instead of taking the conventional gene‐specific approach, a quantitative assessment of the collective expression of all types of dsRNAs expressed in cells may provide more relevant information. Recently, Ali et al reported RNA‐intercalating material‐based biosensor to profile the net expression of cellular dsRNAs. It will be interesting to investigate the potential biomedical application of this dsRNA biosensor in diagnosis and predicting prognosis of degenerative, inflammatory, and autoimmune diseases where the accumulation of dsRNAs are implicated.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Therefore, instead of taking the conventional gene‐specific approach, a quantitative assessment of the collective expression of all types of dsRNAs expressed in cells may provide more relevant information. Recently, Ali et al reported RNA‐intercalating material‐based biosensor to profile the net expression of cellular dsRNAs. It will be interesting to investigate the potential biomedical application of this dsRNA biosensor in diagnosis and predicting prognosis of degenerative, inflammatory, and autoimmune diseases where the accumulation of dsRNAs are implicated.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Previously, we developed an RNA-intercalator based sensor system that could detect total dsRNA expression in cells (Ali et al, 2020). Indeed, the expression of total dsRNAs isolated from HCT116 cells treated with decitabine showed an increasing trend over time (Ali et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we developed an RNA-intercalator based sensor system that could detect total dsRNA expression in cells (Ali et al, 2020). Indeed, the expression of total dsRNAs isolated from HCT116 cells treated with decitabine showed an increasing trend over time (Ali et al, 2019). Together with dsRBP expression, profiling the dynamic induction of total dsRNAs may provide valuable insights toward developing clinical biomarkers to predict the possible outcome of the DNMTi therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] At the same time, examples of photoactive noncovalent nucleic acid binders are rather limited and mainly related to DNA. [5][6][7][8][9][10][11][12][13][14][15] Thus, to the best of my knowledge, there are only a few examples of photoswitchable noncovalent RNAbinders, including the derivatives of benzo-dihydropyrene, 16 spiropyrans 17, 18 and azobenzene-containing peptides. 19 Additionally, these studies were mainly performed on synthetic RNA aptamers.…”
mentioning
confidence: 99%
“…19 Additionally, these studies were mainly performed on synthetic RNA aptamers. Therefore, except for one example, 18 no studies on noncovalent interactions of organic photoswitches with naturally occurring RNAs are available. However, due to their multiple functions in cells, [20][21][22] natural RNAs represent an important target for small organic molecules as analytical probes or therapeutic agents, [23][24][25][26] and the development of novel functional RNA binders is a topical interdisciplinary task.…”
mentioning
confidence: 99%